Kemampuan Mengenal Lambang Bilangan 1-5 Melalui Media Menjepit Angka Pada Anak Usia Dini - Katimah, Kusnul; Dewi Siti Aisyah; Nancy Riana (PAUD Lectura: Jurnal Pendidikan Anak Usia Dini, 2022)
This research was carried out because of the low ability of children to recognize number symbols in TKIT MTA Karawang. For this reason, real action is needed in order to find the right solution related to the ability to recognize number symbols in children, namely through playing with number-clamping media. This study aims to determine whether children's ability to recognize number symbols can be increased through playing with number-clamping media in children aged 4-5 years at TKIT MTA Karawang. The researcher used this type of classroom action research as much as 2 cycles. The subjects in this study were children aged 4-5 years in class A, totaling 15 children, consisting of 11 girls and 4 boys. Based on the results of the study, it is known that there is an increase in the ability to recognize number symbols in children. In the pre-cycle the child's ability to recognize number symbols was 31.39% and increased by 32.52% in the first cycle to 63.91%, the increase again occurred from the first cycle to the second cycle by 18.68%. So that the increase that occurred from the pre-cycle to the second cycle was 82.59%. So it can be concluded that through the media clamping numbers can improve the ability to recognize number symbols.